Answer:
y=7x + 5
Step-by-step explanation:
sub into y= mx + c
where m = slope/gradient (7)
and c = y-value of y-intercept (5)
Hello! You can answer this question by using the distributive property. Basically
a(b+c) = a(b) + a(c)
Let's apply it to this expression:
5x(x-4)
=5x(x)-5x(-4)
Answer:
Step-by-step explanation:
y - 3 = 1/2 (x + 2)
y - 3 = x/2 + 1
y = x/2 + 4
slope: 1/2
y-intercept: (0, 4)
x | y
-8 | 0
0 | 4
Answer:
Answer: log(81)
Decimal Form: 1.90848501
Step-by-step explanation:
This line will land vertically on the -3 line.